The Role of Internal CSR in Promoting Employee Happiness: A Systematic Review of Organizational Cultures - Zaidi, Uzma (Current Progress in Arts and Social Studies Research Vol. 8, 2024)
In the last few decades, Corporate Social Responsibility (CSR) has emerged as a globally resonant subject while gaining substitutional acknowledgement and widespread acceptance across the different sectors of the domains of business, academia and any national or international institute with corporate societies. This systematic review explores the potential effects of organizational culture, with the collaboration of Internal Corporate Social Responsibility (CSR) role on the happiness of employees. The purpose of research is to examine the interaction between organizational culture, specifically CSR and employee well-being in their work lives. By employing systematic analysis and partial least square methodology, the research intends to provide valuable insights into promoting job contentment and dedication to organization. The analysis relies on a partial least square methodology to analyze the CSR and employee relationship. A Boolean formula was applied to filter the research study work for comprehensive systematics analysis results and findings. The key finding of this research is that the clan and adhocracy cultures exert a more pronounced influence on internal CSR whereby flexibility, innovation, and creativity, along with the features of clan culture, such as a focus on employee well-being, autonomy, communication, training, and supervisor support, are found to be positively associated with increased engagement in internal CSR actions. The article presents unprecedented and distinctive additions by establishing a connection between internal CSR, the culture of the organization, and the contentment of employees. Organizations can leverage this connection to develop HR policies and programmes for Employee Happiness. It furnishes significant and valuable perspectives into the precursors of internal CSR and its correlation with the well-being of employees. A limitation of this paper is its nature of secondary review of published sources. Primary research can be conducted to corroborate the findings.